Sooley [large type] - Grisham, John (Random House Large Print, 2021)
After seventeen-year-old Samuel "Sooley" Sooleymon receives a college scholarship to play basketball for North Carolina Central, he moves to Durham from his native, war-torn South Sudan, enrolls in classes, joins the team, and prepares to sit out his freshman season, but Sooley has a fierce determination to succeed so he can bring his family to America, working tirelessly on his game until he dominates everyone in practice, and when Sooley is called off the bench, the legend begins.